Literasi Perdagangan Carbon melalui Blue Economy di Wilayah Pesisir Kabupaten Aceh Timur - M. Iqbal Asnawi; Radhali Radhali; Muhammad Iqbal; Mustika Putra Rokan; Saiful Anwar; Hanri Aldino (El-Mujtama: Jurnal Pengabdian Masyarakat, 2025)
The potential for carbon trading through a blue economy approach in the coastal areas of East Aceh Regency using descriptive qualitative methods through literature studies. The results of the study identified significant blue carbon potential from mangrove ecosystems, which function as effective carbon sinks. However, critical findings revealed that 49.85% of the mangrove area is in a state of severe degradation, not only threatening its ecological function but also potentially releasing stored carbon reserves. The development of a comprehensive and contextual literacy strategy is an important prerequisite for realizing the potential of carbon trading. Integrating the blue economy approach with mangrove conservation programs through a carbon trading mechanism can create synergy between environmental preservation and improving the welfare of coastal communities in East Aceh.